Effect of Packaging on Protein Content, pH, and Sensory of Probiotic Tempeh Juice During Cold Storage - Nur Aini Sahara; Attika Nur Aisah; Maria Erna Kustyawati; Sussi Astuti; Wisnu Satyajaya (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Tempeh juice with probiotics is considered as functional probiotic foods with health benefits. This study aimed to evaluate the effect of packaging type (glass bottle and aluminum foil), and cold storage duration on chemical, microbial and sensory properties of probiotic tempeh juice. The research used a two-factorial Randomized Complete Block Design with three replications. ANOVA was used to analyze the data and it was followed by DMRT test at 5% significance level. The results showed that storage duration had no significant effect on viscosity and other chemical analysis, but was significant on sensory attributes of color, aroma, taste, and overall acceptability. Protein decreased on the 8th day probably due to protein hydrolysis by microbial activity, but increased on the 12th day of storage due to the accumulation of microorganism cell walls during storage. However, sensory changes included a paler color, a stronger fermentation aroma, an acidic alcoholic taste, and overall acceptance was acceptable. It was concluded that glass bottle packaging was more effective in maintaining the stability of protein content, pH, and sensory of probiotic tempeh juice beverage compared to the aluminum foil standing pouch with a spout, with the estimated shelf life was 8 days in cold storage.